2011
DOI: 10.1111/j.1600-6143.2011.03816.x
|View full text |Cite
|
Sign up to set email alerts
|

Living Kidney Donor Follow-Up: State-of-the-Art and Future Directions, Conference Summary and Recommendations

Abstract: In light of continued uncertainty regarding postkidney donation medical, psychosocial and socioeconomic outcomes for traditional living donors and especially for donors meeting more relaxed acceptance criteria, a meeting was held in September 2010 to (1) review limitations of existing data on outcomes of living kidney donors; (2) assess and define the need for long-term follow-up of living kidney donors; (3) identify the potential system requirements, infrastructure and costs of long-term follow-up for living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 36 publications
(41 reference statements)
0
30
0
Order By: Relevance
“…Our DID model showed a pre-policy increase in LDF of 20% per year for 6-month and 1-year LDF and 22% per year for 2-year LDF. These pre-policy increases in LDF may be attributable to the public comment process and consensus conferences (39). Despite increases in LDF, only 43% of centers met all the policy requirements for 2013 LKDs.…”
Section: Discussionmentioning
confidence: 99%
“…Our DID model showed a pre-policy increase in LDF of 20% per year for 6-month and 1-year LDF and 22% per year for 2-year LDF. These pre-policy increases in LDF may be attributable to the public comment process and consensus conferences (39). Despite increases in LDF, only 43% of centers met all the policy requirements for 2013 LKDs.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative approaches to capturing outcomes among representative, diverse samples of living donors are needed. Supplementing the national registry with secondary data sources was endorsed by a consensus conference convened to evaluate ‘Living Kidney Donor Follow-Up: State-of-the-Art and Future Directions' [31] and by individual experts in living donor care [32]. Methodologically, the current study demonstrates the value of pharmacy claims to describe an understudied dimension of health after living kidney donation.…”
Section: Discussionmentioning
confidence: 99%
“…As a reflection of the need for a better understanding of health outcomes specifically among non-white donors, a recent U.S. national consensus conference was convened to evaluate “Living Kidney Donor Follow-up: State-of-the-Art and Future Direction” (5). At this conference, non-white donors were identified as a leading subgroup deserving focused attention.…”
mentioning
confidence: 99%
“…At this conference, non-white donors were identified as a leading subgroup deserving focused attention. Important postdonation outcomes named as focus areas included not only death and terminal renal failure but also chronic medical conditions that may cause kidney damage or bear bidirectional relationships with renal insufficiency, such as hypertension and diabetes mellitus (5). To that end, we recently linked administrative data from a private insurance provider to OPTN donor registration data and observed that, compared with white donors, African American donors had higher risks of postdonation morbidity (6).…”
mentioning
confidence: 99%